Elucidating the Impact of Inhaled Micro-, Nanoplastics from Surgical Face Masks in vitro - LEWIS HODGETTS (2024)
The use of surgical face masks is commonplace throughout medical and occupational settings, but their use was extended to the public during the COVID-19 pandemic, resulting in an influx of manufacture and wastage. These masks are predominantly synthesised from polypropylene (PP), but the complete material list is unknown, and their exact composition varies between suppliers. These single-use masks are known to shed micro,-nanoplastic (MNP) debris directly into the respiratory system, and into the environment upon improper disposal. Plastics in the environment degrade into MNPs over time via several processes, eventually gaining the potential to become airborne. The scenarios of how these mask MNPs could be inhaled, were represented in this project by the use of the innermost layer of mask only (white), and the indirect environmental route; an amalgam of all three mask layers (blue). Despite much focus on the environmental impact of MNPs, the effects these particles could have to human health following inhalation, is largely unknown. Therefore, the aim of this project was to determine the toxicity of PP MNPs, and MNPs derived from face masks representative of two different inhalation exposure scenarios, using an advanced in vitro approach. All synthesized MNPs used a top-down approach; the cryogenic milling of commercial PP powder, 55-75 μm in diameter (purchased from Goonvean Fibres Ltd.), into particles ≤5 μm in diameter. Surgical masks MNPs were synthesized via repeated cryotome slicing. All MNP were characterised via pyrolysis-GC-MS, dynamic light scattering and zeta potential, and further by SEM and STEM-EDX following aerosolisation. NCI-H441 type-II alveolar epithelial cells were cultured at the air-liquid interface, and were exposed to 0.5, 1.0 or 2.0 μg/cm2 of each MNP type for 24 hours. Carbon black (Printex 90) was used as positive particle control. Endpoint analyses of cell death (trypan blue exclusion), barrier integrity (dextran blue), pro-inflammatory response (IL-1β/IL-6/IL-8) and genotoxicity (mononucleate micronucleus) were conducted, alongside Confocal LSM microscopy. STEM-EDX presented each MNP sample to consist predominantly of sodium and chlorine, with lesser expression of carbon, oxygen and titanium. Pyrolysis-GC-MS confirmed dominance of PP content in the tested MNPs, alongside the presence of additives, although this requires further investigation. Both mask MNPs presented significant concentration-dependent increases to IL-8 production and mononucleated micronucleus formation, peaking at 1.0 μg/cm2, but then decreasing at 2.0 μg/cm2 across all respirable MNP samples. Respirable PP MNPs also displayed similar trends to the mask MNPs, but these were not statistically significant findings. Current data therefore suggests that inhalation of MNPs do have the potential to produce hazardous responses to alveolar models in vitro. Future developments should improve on the realism of the model by the incorporation of immune cell co-culturing. To improve endpoint analysis, the introduction of oxidative stress evaluation and gene expression is necessary, in addition to the validation of a suitable genotoxic assay protocol for NCI-H441 cells.